Comprehensive Assessment of Quality Index of Groundwater of Selected Government Schools in Patna District of Bihar, India - Kumar, Jayant; Kumar, Amit; Anand, Akshay; Raj, Nikhil; Pandey, Shekhar; Kumar, Rishav; Raj, Harsh; Gangwar, Tripti (International Journal of Environmental Sciences, 2025)
Purpose: This study assesses groundwater quality in Government Schools of Patna, Bihar, with a focus on its impact on student health and education. Groundwater, a critical resource for drinking and sanitation, is increasingly compromised by urbanization, industrialization, and inadequate waste management. Methodology: Utilizing the Groundwater Quality Index (GWQI), water samples from schools were analyzed for parameters such as pH, total dissolved solids (TDS), alkalinity, conductivity, total hardness, calcium, magnesium, sulphate, nitrate, chloride, fluoride, and iron ion concentrations were analysed using standard devices. A correlation matrix of twelve parameters, among themselves and with water quality index (WQI) was constructed. Findings: The values of all parameters were within the permissible limits (BIS: 2012) except iron concentration was found to be exceeding the prescribed standard limit. WQI has revealed the suitability of most of water samples for drinking not in all samples collected from fourteen different Government Schools. As findings revealed significant contamination in few schools, posing health risks, these issues adversely affect student attendance and academic outcomes. Unique contribution to Theory, Practice and Policy: This research aligns with Sustainable Development Goal 6, aiming to ensure clean water access and underscores the urgent need for sustainable groundwater management in educational institutions. The results serve as a call to action for policymakers, educators, and stakeholders to prioritize water quality improvements, safeguarding children's health and fostering a conducive learning environment.